Casirivimab/Imdevimab for Active COVID-19 Pneumonia Which Persisted for Nine Months in a Patient with Follicular Lymphoma during Anti-CD20 Therapy - Nagai, Hiroyuki; Saito, Makoto; Adachi, Eisuke; Sakai-Tagawa, Yuko; Yamayoshi, Seiya; Kiso, Maki; Kawamata, Toyotaka; Koga, Michiko; Kawaoka, Yoshihiro; Tsutsumi, Takeya; Yotsuyanagi, Hiroshi (Japanese Journal of Infectious Diseases, 2022)
Immunocompromised patients are more likely to develop severe COVID-19, and exhibit high mortality. It is also hypothesized that chronic infection in these patients can be a risk factor for developing new variants. We describe a patient with prolonged active infection of COVID-19 who became infected during treatment with an anti-CD20 antibody (obinutuzumab) for follicular lymphoma. This patient had persistent RT-PCR positivity and live virus isolation for nine months despite treatment with remdesivir and other potential antiviral therapies. The computed tomography image of the chest showed that the viral pneumonia repeatedly appeared and disappeared in different lobes, as if a new infection had occurred continuously. The patient’s SARS-CoV-2 antibody titer was negative throughout the illness, even after two doses of the BNT162b2 mRNA vaccine were administered in the seventh month of infection. A combination of monoclonal antibody therapy against COVID-19 (casirivimab and imdevimab) and antivirals resulted in negative RT-PCR results, and the virus was no longer isolated. The patient was clinically cured. During the 9-month active infection period, no fixed mutations in the spike (S) protein were detected, and the in vitro susceptibility to remdesivir was retained. Therapeutic administration of anti-SARS-CoV-2 monoclonal antibodies is essential in immunocompromised patients. Therefore, measures to prevent resistance against these key drugs are urgently needed.